Identifying academic success and underperformance: The discriminative power of very short answer questions and multiple-choice questions - Elise V. van Wijk; Floris M. van Blankenstein; Bastian N. Ruijter; Jos H. T. Rohling; Jolein van der Kraan; Friedo W. Dekker; Alexandra M. J. Langers (PLoS ONE, 2026)
Background Multiple-choice questions (MCQs) are widely used in medical education, but are criticized for cueing and guessing. Very short answer questions (VSAQs), which require students to generate responses independently, may better assess knowledge. While VSAQs demonstrate higher item discrimination within individual exams, their effectiveness in distinguishing academic performance across multiple assessments remains unclear – representing a key gap in the validation of VSAQs under Messick’s framework, specifically the category of “ relations to other variables ”. This study examines whether VSAQs or MCQs more effectively distinguish students of varying performance levels across multiple summative examinations. Methods We analyzed retrospective data from six mixed-format examinations with VSAQs and MCQs of three cohorts of first- and second-year medical students. Academic performance was measured using grade point average (GPA) across assessments. Linear regression assessed the relationship of each question format with GPA, while ROC curves and C-statistics evaluated their ability to identify poor and excellent performing students (lowest and highest quintile of GPA). Results VSAQs showed higher item discrimination (R ir -values) than MCQs in all exams. VSAQs also had a stronger positive association with GPA compared to MCQs, and higher C-statistics, indicating superior discriminative ability. Conclusion VSAQs outperform MCQs in distinguishing academic performance levels across multiple assessments. Their integration into examinations enhances discriminative ability and may facilitate earlier identification of poor and excellent performing students, enabling targeted interventions and support of students.